2016
DOI: 10.7150/thno.16587
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Trafficking Network of Protein Nanocapsules: Endocytosis, Exocytosis and Autophagy

Abstract: The inner membrane vesicle system is a complex transport system that includes endocytosis, exocytosis and autophagy. However, the details of the intracellular trafficking pathway of nanoparticles in cells have been poorly investigated. Here, we investigate in detail the intracellular trafficking pathway of protein nanocapsules using more than 30 Rab proteins as markers of multiple trafficking vesicles in endocytosis, exocytosis and autophagy. We observed that FITC-labeled protein nanoparticles were internalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 42 publications
2
62
0
Order By: Relevance
“…The 45 nm AuNPs were chosen since they exhibited the best pro-osteogenic effect among the three sizes. 3-MA blocks the formation of autophagosome by inhibiting the class III phosphatidylinositol 3-kinase, and CQ inhibits autophagy at a later step by blocking the degradation of autolysosome 45, 47. Both 3-MA and CQ significantly reversed the osteogenesis enhanced by 45 nm AuNPs, suggesting the pro-osteogenic effect of 45 nm AuNPs was related to the activation of autophagy, which is consistent with the previous studies 19-23.…”
Section: Discussionsupporting
confidence: 89%
“…The 45 nm AuNPs were chosen since they exhibited the best pro-osteogenic effect among the three sizes. 3-MA blocks the formation of autophagosome by inhibiting the class III phosphatidylinositol 3-kinase, and CQ inhibits autophagy at a later step by blocking the degradation of autolysosome 45, 47. Both 3-MA and CQ significantly reversed the osteogenesis enhanced by 45 nm AuNPs, suggesting the pro-osteogenic effect of 45 nm AuNPs was related to the activation of autophagy, which is consistent with the previous studies 19-23.…”
Section: Discussionsupporting
confidence: 89%
“…Most NPs, such as PLGA NPs, micelles, chitosan NPs, and microgels, can be entrapped by this classical degradation system. 29 Nevertheless, the cytoplasm of RWM is not the destination of NPs. NPs should escape from lysosomes, and as many NPs as possible should move across the RWM into the perilymph.…”
mentioning
confidence: 99%
“…The binding complex, UVRAG–Beclin1, activates Class III PI3K to elicit both endosome and autophagy pathway. A recent report demonstrates that the bovine serum albumin nanocapsules (nBSA) are internalized into cell through the Rab34‐regulated macropinocytosis and Arf6‐mediated clathrin‐ and caveolae‐independent endocytosis, which also illustrates the crosstalk relationship between endocytosis and autophagy . It was shown that the internalized nBSA led to the elevated level of LC3‐II and were degraded by autophagy pathway.…”
Section: Endocytosis Pathways Of Nmsmentioning
confidence: 99%
“…They are perfect vesicle markers for investigating the details of intracellular trafficking pathway of the NMs. For examples, Rab5 involving in endocytic internalization and early endosomes' fusion is an early endosome marker, Rab7 relating to control late endocytic trafficking is a late endosome maker, and Rab9 participates in cargo recycling from endosomes to the trans‐Golgi network . Additionally, Rab proteins also play a vital role in the mediation of autophagic process .…”
Section: Endocytosis Pathways Of Nmsmentioning
confidence: 99%